Avaliação da implementação do programa bolsa família no município de Lavras: uma análise a partir do modelo do Hexágono Sistêmico - Magalhães, Juliana Moreira (2020)
The Bolsa Família Program (PBF) has become a world reference in income transfer programs, and is one of the main national references for social programs to reduce socioeconomic inequality. In this sense, the present work has the general objective of analyzing the implementation of the Bolsa Família Program in the municipality of Lavras. To analyze this implementation, this study made a methodological choice for the Systemic Hexagon, by Jannuzzi. A bibliographic research was carried out on the subject, document analysis, in addition to the non-participant observation in the Reference Centers in Social Assistance and interviews with public managers. The results identified the bottlenecks of the PBF in Lavras, and several suggestions for improvements were also highlighted, which can be used in other municipalities. The Map of Processes and Results was also prepared, as a research program for evaluating the PBF in the municipality of Lavras.